Analisis Jumlah Tenaga Pengajar Dan Kepala Sekolah Berdasarkan Kelompok Umur Di Provinsi Maluku, Maluku Utara, Sulawesi Barat, Dan Bangka Belitung Tahun 2023/2024 - Rosyani, Perani; Rizki, Anggoro; Kholik, Abdul; Zidan, Ahmad (CV. Shofanah Media Berkah, 2024)
The background of the condition of Indonesia's territory is very wide so that to find out the data on the number of teaching staff, it is necessary to analyze the number of school principals and the number of teaching staff on the islands of Maluku, North Maluku, Bangka Belitung and West Sulawesi for the period of November 16, 2023/2024. The problem that occurs today is the lack of information about the number of educators based on age groups caused by the very wide difference in geographical conditions in Indonesia, therefore, this study aims to find out the age distribution of teaching staff in various provinces. In this study, we have also selected based on school status, either public schools or private schools. Through the calculation of averages, histograms, frequency polygons, ogive which is expected to be knowledge for students in Indonesia.